Collaborating, Learning, and Adapting Framework & Key Concepts (USAID)
Although collaborating, learning, and adapting (CLA) are not new to US AID, they often do not happen regularly or systematically and are not intentionally resourced. The CLA framework above identifies components and subcomponents to help you think more deliberately about what appr oach to CLA might be best tailored to your organizational or project c ontext. The framework recognizes the diversity of what CLA can look li ke in various organizations and projects while also giving CLA structu re, clarity, and coherence across two key dimensions: CLA in the Progr am Cycle: how CLA is incorporated throughout Program Cycle processes, including strategy, project, and activity design and implementation; a nd Enabling Conditions: how an organization’s culture, business proces ses, and resource allocation support CLA integration. Organizations ne ed both integrated CLA practices appropriate for their context and con ducive enabling conditions to become stronger learning organizations c apable of managing adaptively. The framework stresses the holistic and integrated nature of the various components of CLA to reinforce the p rinciple that CLA is not a separate workstream—it should be integrated into existing processes to strengthen the discipline of development a nd improve aid effectiveness.